Penerapan learning Management Systems (LMS) berbantuan Sevima Edlink: Efektifkah dalam menunjang Perkuliahan Daring? - Enggal Mursalin; Aria Bayu Setiaji; Eman Wahyudi Kasim (Jurnal Pendidikan Edutama, 2022)
Abstract: The Covid-19 pandemic requires IAIN Ambon to change lectures from face-to-face to online by implementing Learning Management Systems assisted by SEVIMA EdLink. This survey study aims to determine the perception of students of the Tadris IPA Study program of IAIN Ambon towards the application of the SEVIMA EdLink-assisted LMS in the odd semester lectures of the 2020/2021 academic year. A total of 34 students were given a questionnaire related to the implementation of the online lecture. The data from the questionnaires were then analyzed using a descriptive-quantitative percentage technique. The results of data analysis revealed that as many as, 1) 82.3% of students stated that the features on SEVIMA EdLink were easy to understand and use in supporting lectures; 2) 79.5% of students are satisfied with the application of SEVIMA EdLink in online lectures, and 3) 73.5% of students agree that the SEVIMA EdLink will continue to be applied to support online lectures. Some of the obstacles expressed by students were the limited internet network at their residence and the increased expenditure for purchasing internet packages, so it was hoped that the campus could program tuition subsidies in the form of assistance in purchasing internet packages.Keywords: LMS, SEVIMA EdLink, Online Lecture, Student Perception, Covid-19 Pandemic  Abstrak: Pandemi Covid-19 menuntut IAIN Ambon mengubah perkuliahan dari tatap muka menjadi daring dengan menerapkan Learning Management Systems (LMS) berbantuan SEVIMA EdLink. Penelitian survei ini bertujuan untuk mengetahui persepsi mahasiswa Prodi Tadris IPA IAIN Ambon terhadap penerapan LMS berbantuan SEVIMA EdLink pada perkuliahan semester ganjil Tahun Ajaran 2020/2021. Sebanyak 34 mahasiswa diberikan kuesioner terkait pelaksanaan perkuliahan daring tersebut. Data hasil pengisian kuesioner kemudian dianalisis menggunakan teknik deskriptif-kuantitatif persentase. Hasil analisis data mengungkapkan bahwa sebanyak, 1) 82,3% mahasiswa menyatakan fitur pada SEVIMA EdLink mudah dipahami dan digunakan dalam menunjang perkuliahan; 2) 79,5% mahasiswa puas dengan penerapan SEVIMA EdLink dalam perkuliahan daring; dan 3) 73,5% mahasiswa setuju SEVIMA EdLink diterapkan seterusnya untuk menunjang perkuliahan daring. Beberapa kendala yang diungkapkan oleh mahasiswa yakni terbatasnya jaringan internet di tempat tinggalnya dan bertambahnya pengeluaran untuk pembelian paket internet, sehingga diharapkan pihak kampus dapat memprogramkan subsidi biaya perkuliahan dalam bentuk bantuan pembelian paket internet.Kata kunci: LMS, SEVIMA EdLink, Perkuliahan Daring, Persepsi Mahasiswa, Pandemi Covid-19